In the Unlikeliest of Places : How Nachman Libeskind Survived the Nazis, Gulags, and Soviet Communism - Berkovits, Annette Libeskind, 1943- (Book collections on Project MUSE., 2014)
With just a box of tapes, Annette Libeskind Berkovits tells more than her father's story: she builds an uncommon family saga and reimagines a turbulent past.